2019
DOI: 10.2147/ott.s182242
|View full text |Cite
|
Sign up to set email alerts
|

<p>Up-regulation of CKAP2L expression promotes lung adenocarcinoma invasion and is associated with poor prognosis</p>

Abstract: Aim The purpose of this study is to consider the function of cytoskeleton-associated protein 2-like (CKAP2L) in lung adenocarcinoma (LAD) development and its prognostic value. Methods The mRNA expression of CKAP2L and its correlation with clinical factors in LAD patients were analyzed from the data taken from The Cancer Genome Atlas and The First Affiliated Hospital of Kunming Medical University. We constructed H460 and A549 cell lines with silenced CKAP2L using RNA int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…According to the published literature, little is known about the role of CKAP2L in tumor development and proliferation. A recent paper reports high expression of CKAP2L, which induces the invasion of lung adenocarcinoma by the MAPK signaling pathway, and shows correlation with poor prognosis ( Xiong et al, 2019 ). Furthermore, CKAP2 acts as a significant paralog of CKAP2L, and the oncogenic nature and overexpression of this gene is revealed in PCa ( Yu et al, 2015 ), ovarian cancer ( Gao et al, 2017 ), and glioma ( Wang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the published literature, little is known about the role of CKAP2L in tumor development and proliferation. A recent paper reports high expression of CKAP2L, which induces the invasion of lung adenocarcinoma by the MAPK signaling pathway, and shows correlation with poor prognosis ( Xiong et al, 2019 ). Furthermore, CKAP2 acts as a significant paralog of CKAP2L, and the oncogenic nature and overexpression of this gene is revealed in PCa ( Yu et al, 2015 ), ovarian cancer ( Gao et al, 2017 ), and glioma ( Wang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, CKAP2L has been proved to be a vital component of centrosome and is situated in the spindle, the midbody and the spindle pole . A recent study revealed that high expression of CKAP2L promoted the invasion of lung cancer through MAPK signalling pathway and was associated with poor prognosis . In addition, the oncogenic nature of CKAP2, which is an important paralog of CKAP2L, has also been illustrated in ovarian cancer, glioma and breast cancer .…”
Section: Discussionmentioning
confidence: 99%
“…e high expression of CKAP2L in lung adenocarcinoma was found to be associated with the tumor stage, lymph node status, and metastasis. It has been reported that CKAP2L may act on the proliferation, migration, and invasion of lung adenocarcinoma cells through mitogen-activated protein kinase (MAPK) signaling pathway [26], but its role in other tumors has yet to be fully studied. To our knowledge, the present study provided the first demonstration that CKAP2L may be related to PCPG metastasis.…”
Section: Discussionmentioning
confidence: 99%